Financial Inclusion on Indonesia's Financial System Stability: The Role Intervening of Financial Technology - I Dewa Made Endiana; Luh Komang Merawati (Jurnal Keuangan dan Perbankan, 2022)
This study aims to express the concept of thinking related to in-depth financial development through financial inclusion with the intervention of new technological developments which are expected to have a positive impact on increasing the stability of Indonesia's financial system. This study uses the Estimation Error Correction Model (ECM). Banking instruments represented by international investment banking have a significant effect in the long term on the stability of the Indonesian financial system. Then on financial inclusion instruments, the number of financial office services has a significant influence on NPL performance which reflects the performance of the financial system. Fintech instruments that encourage financial inclusion, such as the number of ATMs and e-money, do not have a significant impact on financial system stability. Policy recommendations that can be made can be through fintech socialization as a form of financial integration to achieve speed, effectiveness and efficiency of access to unbanked communities. In addition, in the short term, as the socialization and realization of fintech processes are integrated into the unbankable community, the construction of bank branches as financial service offices also needs to be carried out as an effort to expand the deepening of access to financial information and services